Performance of individually measured vs population‐based C‐peptide kinetics to assess β‐cell function in the presence and absence of acute insulin resistance. Issue 3 (27th September 2017) - Varghese, Ron T.; Dalla Man, Chiara; Laurenti, Marcello C.; Piccinini, Francesca; Sharma, Anu; Shah, Meera; Bailey, Kent R.; Rizza, Robert A.; Cobelli, Claudio; Vella, Adrian
Abstract : Aims: To compare the performance of population‐based kinetics with that of directly measured C‐peptide kinetics when used to calculate β‐cell responsivity indices, and to study people with and without acute insulin resistance to ensure that population‐based kinetics apply to all conditions where β‐cell function is measured. Methods: Somatostatin was used to inhibit endogenous insulin secretion in 56 people without diabetes. Subsequently, a C‐peptide bolus was administered and the changing concentrations were used to calculate individual kinetic measures of C‐peptide clearance. In addition, the participants were studied on 2 occasions in random order using an oral glucose tolerance test (OGTT). On one occasion, free fatty acid elevation, to cause insulin resistance, was achieved by infusion of Intralipid + heparin. The Disposition Index (DI) was then estimated by the oral minimal model using either population‐based or individual C‐peptide kinetics. Results: There were marked differences in the exchange variables ( k 12 and k 21 ) of the model describing C‐peptide kinetics, but smaller differences in the fractional clearance; that is, the irreversible loss from the accessible compartment ( k 01 ), obtained from population‐based estimates compared with experimental measurement. Because it is predominantly influenced by k 01, DI estimated using individual kinetics correlated well with DI estimated using population‐based kinetics. Conclusions: These data support the use of population‐based measures of C‐peptide kinetics to estimate β‐cell function during an OGTT.